Pediatric fibrous pseudotumor of the tunica vaginalis testis - Ryan Yu; Jefferson Terry; Mutaz Alnassar; Jorge Demaria (Asian Journal of Urology)
We describe a 16-year-old male with ultrasound evidence of a 1.3 cm right paratesticular nodule, which was managed by intraoperative frozen section and excisional biopsy. The pathologic findings were consistent with benign fibrous pseudotumor of the tunica vaginalis testis, which is a very rare lesion in the pediatric population. Consideration of fibrous pseudotumor in the differential diagnosis of pediatric paratesticular masses may help prevent unnecessarily aggressive therapy. Keywords: Adolescent, Testis, Ultrasonography, Pathology